METHOD OF ESTIMATION OF MORTALITY RATES FROM LENGTH SAMPLES - Srinath, M; Alagaraja, K (Indian Journal of Fisheries, 2011)
Taking the probable distribution of age of fish as given by Ssentango and; Larkin (1973), and considering the size distribution as available from the d’ to without taking recourse to the assumption of Marten (1978), a model is dtevelopsd to get an estimate of ’Z’. A table is appended to facilitate the estimation